Mutations in SLC35A3 cause autism spectrum disorder, epilepsy and arthrogryposis. Issue 11 (12th September 2013) - Edvardson, Simon; Ashikov, Angel; Jalas, Chaim; Sturiale, Luisa; Shaag, Avraham; Fedick, Anastasia; Treff, Nathan R; Garozzo, Domenico; Gerardy-Schahn, Rita; Elpeleg, Orly
Abstract : Background: The heritability of autism spectrum disorder is currently estimated at 55%. Identification of the molecular basis of patients with syndromic autism extends our understanding of the pathogenesis of autism in general. The objective of this study was to find the gene mutated in eight patients from a large kindred, who suffered from autism spectrum disorder, arthrogryposis and epilepsy. Methods and results: By linkage analysis and exome sequencing, we identified deleterious mutations in SLC35A3 in these patients. SLC35A3 encodes the major Golgi uridine diphosphate N -acetylglucosamine (UDP-GlcNAc) transporter. In Golgi vesicles isolated from patient fibroblasts the transport of the respective nucleotide sugar was significantly reduced causing a massive decrease in the content of cell surface expressed highly branched N -glycans and a concomitant sharp increase of lower branched glycoforms. Conclusions: Spontaneous mutation in SLC35A3 has been discovered in cattle worldwide, recapitulating the human phenotype with arthrogryposis and additional skeletal defects known as Complex Vertebral Malformation syndrome. The skeletal anomalies in the mutant cattle and in our patients, and perhaps even the neurological symptoms are likely the consequence of the lack of high-branched N -glycans and the concomitant abundance of lower-branched glycoforms at the cell surface. This pattern has previously been associated with growth arrest and induction of differentiation. With this study, we add SLC35A3 to the gene list of autism spectrum disorders, and underscore the crucial importance of UDP-GlcNAc in the regulation of the N -glycan branching pathway in the Golgi apparatus.